2018
DOI: 10.3389/fpls.2018.01631
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Effectivity of Dual and Tripartite Associations on Soybean (Glycine max L. Merr.) Cultivars Inoculated With Bradyrhizobium japonicum and AM Fungi

Abstract: Soybean (Glycine max L. Merr.) is regarded worldwide as indisputably one of the most important crops for human food and animal feed. The presence of symbiotic bacteria and fungi is essential for soybean breeding, especially in low-input agricultural systems. Research on the cooperation between different microbial symbionts is a key to understanding how the health and productivity of the plant is supported. The symbiotic effectivity of dual and tripartite symbiotic agents was investigated in two pot experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Rhizobia inoculation has been regarded as a sustainable and cost-effective technology to augment the plants' N needs (Ondieki et al, 2017). Several studies have reported that inoculation with rhizobia improves legume growth, nutrition, and production (Takács et al, 2018;Aserse et al, 2020). However, inoculation with proven rhizobia inoculants as well as some commercial inoculants has at times failed to yield positive results when inoculation is done in regions with different agroenvironmental conditions to the original habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobia inoculation has been regarded as a sustainable and cost-effective technology to augment the plants' N needs (Ondieki et al, 2017). Several studies have reported that inoculation with rhizobia improves legume growth, nutrition, and production (Takács et al, 2018;Aserse et al, 2020). However, inoculation with proven rhizobia inoculants as well as some commercial inoculants has at times failed to yield positive results when inoculation is done in regions with different agroenvironmental conditions to the original habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Legumes can form tripartite symbiotic associations with nodule-inducing rhizobia and AMF, that may benefit growth, development, and the uptake of both phosphorous and nitrogen [16][17][18][19]. It was shown in soybean and common bean (Phaseolus vulgaris L.) that the co-inoculation of AMF and rhizobium improved production, efficiency of photosynthesis, nodulation and, especially, an increase in both phosphorus and nitrogen concentrations [20,21]. In addition, some studies showed that co-inoculation of soybean with PGPR of Bacillus species and the rhizobia Bradyrhizobium japonicum, increases nodulation and nitrogen fixation [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…Garbaye proposed five potential mechanisms underlying the MHB effect: (i) Enhancement of plant susceptibility to mycorrhizal colonization, (ii) enhancement of the root-fungus recognition process, (iii) nutritional improvement of fungal growth, (iv) a beneficial change in the composition of the rhizosphere soil, and (v) stimulation of fungal propagules germination [7]. It has been proposed that active bacterial attachment and colonization of the mycorrhizal surfaces are required for MHB to influence mycorrhizal plant growth and health [8,9]. Streptomycetes studies demonstrated that the exudation of bacterial compounds can both inhibit pathogenic fungi growth and support symbiotic fungi growth [10,11].…”
Section: Introductionmentioning
confidence: 99%